Computational Studies and Synthesis of New Heterocyclics as CNS Agents - Saini, Pooja; Kumar, Sushil (Current Drug Discovery Technologies, 2024)
Aim: This research work aimed to design and synthesize some new molecules of phenothiazine. The work’s emphasis was on forming new phenothiazines in two series, 1-(10H-phenothiazin- 10-yl)-2-((4-(1-(phenylimino)ethyl)phenyl)amino)ethan-1-one derivatives (4a-4j) and 1-(4-((2-oxo-2- (10H-phenothiazin-10-yl)ethyl)amino)phenyl)-3-phenylprop-2-en-1-one derivatives (P1-P5). Methods: Chloroacetylation of phenothiazine was done to afford 2-chloro-1-(10H-phenothiazin-10- yl)ethan-1-one, which was further reacted with 4-amino acetophenone to produce 2-((4- acetylphenyl)amino)-1-(10H-phenothiazin-10-yl)ethan-1-one. Then, it was treated with substituted anilines and substituted benzaldehydes to produce the final derivatives 4a-4j and P1-P5, respectively. Results: All 15 derivatives (4a-4j and P1-P5) were characterized by evaluating their Rf value, melting point, solubility, IR spectroscopy, and 1HNMR spectroscopy. Molecular docking was performed by using AutoDock Vina v.1.2.0 (The Scripps Research Institute, La Jolla, CA, USA) docking software, and the anxiolytic activity of the derivatives was assessed by using the elevated plus maze model. Conclusion: The designed scheme was executed in the departmental laboratory. The chemical structure of the compounds was confirmed on the basis of TLC, IR, and 1HNMR analyses. The docking study revealed a good docking score of the compounds. The Log P value of the compounds indicated their good penetration into CNS. The compounds were also screened for anxiolytic activity. Among them, compounds 4f, 4h, and P3 showed maximum activity as anti-anxiolytic agents.
Keywords: aromatic molecules